2016
DOI: 10.1017/jfm.2016.358
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-flame flickering as a hydrodynamic global mode

Abstract: The present study employs a linear global stability analysis to investigate buoyancyinduced flickering of axisymmetric laminar jet diffusion flames as a hydrodynamic global mode. The instability-driving interactions of the buoyancy force with the density differences induced by the chemical heat release are described in the infinitely fast reaction limit for unity Lewis numbers of the reactants. The analysis determines the critical conditions at the onset of the linear global instability as well as the Strouhal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…The discrepancies between the two analyses can be attributed to the rapid spatial development of the flow (see figure 2(a)) that violates the parallel flow hypothesis on which the local analysis is based. An clear example of this was found recently by Moreno-Boza et al (2016) when studying buoyancy-driven flickering in diffusion flames.…”
Section: The Isolated Modementioning
confidence: 71%
“…The discrepancies between the two analyses can be attributed to the rapid spatial development of the flow (see figure 2(a)) that violates the parallel flow hypothesis on which the local analysis is based. An clear example of this was found recently by Moreno-Boza et al (2016) when studying buoyancy-driven flickering in diffusion flames.…”
Section: The Isolated Modementioning
confidence: 71%
“…Recent analyses have shown that the flickering of low-density jets [36] , jet diffusion flames [30] , and buoyant plumes [37,38] is a manifestation of a hydrodynamic global instability, the onset of which can be computed with a linear global stability analysis. The same type of global instability is anticipated to be responsible for the puffing of liquid-pool fires.…”
Section: Puffing As a Hydrodynamic Global Modementioning
confidence: 99%
“…It is known that the buoyant acceleration of the flow in the central region of the flame causes the radial profiles of axial velocity to exhibit inflection points along the flame envelope, a region characterized by low values of the advection velocity [30,42,43] . From a local stability point of view, this scenario allows for the possibility of an absolutely unstable flow.…”
Section: Computations Of Steady Liquid-pool Flamesmentioning
confidence: 99%
See 2 more Smart Citations